Genetics analysis of apical dominance and improvement of suckering behaviour in plantain - Ortíz, R.; Vuylsteke, D.R. (1994)
Apical dominance, i.e., the inhibition of lateral bud growth due to growth substances released by the terminal bud, has been considered as a limiting factor for the perennial productivity of plantains (Musa spp., AAB group).Segregation ratios in F1and F2plantain–banana hybrids suggest that inheritance of apical dominance is controlled by a major recessive gene, ad. The dominant Ad allele improved the suckering of plantain-banana hybrids, as measured by the height of the tallest sucker at flowering and harvest. At harvest, the ratoon crop of the diploid and tetraploid hybrids had completed 70% to 100% of its vegetative development, whereas the ratoon of the plantain parents, due to high apical dominance, was only at 50% of total pseudostem growth. Sucker growth rates are generally the result of gibberellic acid (GA3) levels, and it is suggested that the Ad gene regulates GA3production. However, the Ad gene has in complete penetrance, genetic specificity, and variable expressivity. Increased frequency of the Ad gene and a commensurate improvement in the suckering behavior of the diploid populations may be achieved by phenotypic recurrent selection.